Kesulitan yang Dihadapi oleh Mahasiswa dalam Studi di Program Sarjana - Mulyadi Guntur Waseso (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The study was aimed at exploring problems faced by undergraduate students in their study. Sixty five students of Nonformal Education Department of IKIP Malang were purposively selected. A closed questionnaire was used to collect the data, which were then analyzed using Q-short technique and Spearman’s rank order correlation. The findings suggest that there were a number of problems faced by the students in their study, for instance, understanding textbooks written in English, writing papers, writing up reports of practice teaching and field study, conducting effective group discussion, and problems related to social relationships/love, health, and conditions of places where they lived. There was a positive relationship of problem type between male and female students.